1984
DOI: 10.1021/np50034a014
|View full text |Cite
|
Sign up to set email alerts
|

Rollinone, a New Cytotoxic Acetogenin from Rollinia papilionella

Abstract: Rollinone, a new member of a series of cytotoxic, linear acetogenins bearing a bistetrahydrofuran moiety and a gamma-lactone, has been isolated from Rollinia papilionella. The structure elucidation of rollinone was achieved by interpretation of the pmr and cmr data and mass spectral fragmentation patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…In a previous publication we reported the isolation and identification of two acetogenins from A. cherimolia seeds: cherimoline (5) and 2,35-dihydrocherimoline (18). They may be regarded as two new metabolites of fatty acids, and their fundamental structure (bis-tetrahydrofuran y-lactones) was identified for the first time in Uvaria acuminata roots (28,29) and more recently in other species from Annonaceae (30)(31)(32)(33)(34)(35). The spectral data of lactone 6, laherradurine, are similar to those of 2,35-dihydrocherimoline (18).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous publication we reported the isolation and identification of two acetogenins from A. cherimolia seeds: cherimoline (5) and 2,35-dihydrocherimoline (18). They may be regarded as two new metabolites of fatty acids, and their fundamental structure (bis-tetrahydrofuran y-lactones) was identified for the first time in Uvaria acuminata roots (28,29) and more recently in other species from Annonaceae (30)(31)(32)(33)(34)(35). The spectral data of lactone 6, laherradurine, are similar to those of 2,35-dihydrocherimoline (18).…”
Section: Resultsmentioning
confidence: 99%
“…The use of the phenylthio moiety not only activates the lactone ring for alkylation but also provides a suitable functional group for later elimination to form the double bond of the butenolide ring of ancepsenolide (1). Reaction of "y-valerolactone (2) with lithium diisopropylamide (LDA) in hexamethylphosphoramide (HMPA), followed by the addition of diphenyl disulfide resulted in a 52% yield of 5-methyl-3-(phenylthio)dihydro-2(3H)-furanone (3) as a mixture of diastereomers in an approximate ratio of 1:1 (7,8). Since the phenylthio moiety is eliminated in a later step, the diastereomers of 3 were not separated, and the mixture was used in the alkylation.…”
Section: Resultsmentioning
confidence: 99%
“…During the past few years, several examples of cytotoxic linear C34 acetogenins containing a bistetrahydrofuran ring system have been reported (1)(2)(3)(4). One characteristic feature of these naturally occurring acetogenins is the presence of a ' -methyl-'ybutyrolactone (5-methyl-2-furanone) moiety as either a butenolide or a butanolide linked to the bistetrahydrofuran system by a 13or 14-carbon chain.…”
mentioning
confidence: 99%
“…Over the past seven years, investigations of several genera of the Annonaceae have resulted in the characterization of a number of novel linear acetogenins containing one or two tetrahydrofuran rings, a terminal "y-lactone, and several hydroxyl moieties (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). One of the most recent reports by Yui et al (11) has caused us to reexamine the structure of rollinone that we reported in 1984 (3).…”
mentioning
confidence: 90%
“…The relative stereochemistry around the bistetrahydrofuran moiety of 2 was established by the method of Hoye and coworkers (14,15). The diacetate derivative 3 of rollinone [2] was prepared as in Dabrah and Sneden (3) and analyzed by 1H nmr at 300 MHz. The acetate resonances appeared at 2.052 and 2.076, establishing one erythro and one threo relationship between the tetrahydrofuran rings and adjacent oxygenated carbons.…”
mentioning
confidence: 99%